Draft Genome Sequences of Bacterial Strains Capable of Degrading Ulvan from the Green Alga Ulva ohnoi - Mondal, Ratna (Microbiol Resour Announc, 2020)
We present here the draft genome sequences of four marine bacterial strains which can use ulvan as their sole carbon source. We used ulvan extracted from the green alga Ulva ohnoi. Each bacterium contains a polysaccharide-utilizing locus, which is necessary for the complete degradation of ulvan.